Repetitive transcranial magnetic stimulation in Aphasia and communication impairment in Post-Stroke: Systematic review of literature (2016)
Background: Post-stroke aphasia is one of the major disabilities and a risk factor for other complications, is also associated with increased mortality, depression and impairments in communication. Repetitive Transcranial Magnetic Stimulation (rTMS) is an alternative. We propose the review of literature published until now of rTMS. Methods: We included articles published on PubMed and EMBASE, we included studies if were: randomized controlled blinded clinical trials, meta-analyses or crossover designs of rTMS alone or with speech therapy or any other therapy tested with rTMS. One author included these if: report baseline assessment and one or more posterior assessments; overall results and subtest report; statistically significant results showed by p value. We also assessed the risk of bias of each article. Main results: We included 15 articles, the average age was62.42 ± 4.04; most used low frequency stimulation (1 Hz), most used a coil of 70mm, 77% applied 10 sessions, most did a Speech language therapy. From overall test result:66% studies improved Aphasia; room subtest results: only 1 study improved listening, speaking and reading; 2 studies improved writing, 80% studies improved naming skills, Two studies improved writing and description, 3 studies improved compression and expression, 46% improved repetition.47% of studies used Boston battery, 33% used Aachen Aphasia Test. Conclusions: The articles included showed improvement of scale results for aphasia in post-stroke patients, mainly due to improvement in naming and repetition skills.